2022
DOI: 10.1037/xhp0001013
|View full text |Cite
|
Sign up to set email alerts
|

Social relevance modulates multisensory integration.

Abstract: When interacting with the environment, humans exhibit robust biases toward information that pertains to themselves: Self-relevant information is processed faster and yields more accurate responses than information linked to others. Recent studies have shown that simple social associations can lead to the instant deployment of this benefit in the processing of abstract stimuli. However, how self-prioritization evolves across the processing hierarchy has been a subject of intense debate. Furthermore, there is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 123 publications
2
35
0
Order By: Relevance
“…While the findings of the present study align with the mixed evidence of SPE arising at perceptual levels of information processing (Constable, Rajsic, et al, 2019; Golubickis et al, 2018; Macrae et al, 2017; Reuther & Chakravarthi, 2017; Sui et al, 2012; Stein et al, 2016), they suggest that part of the mixed findings regarding perceptual effects on self-prioritization may hinge on use of specific stimuli. At the same time, due to the online nature of the study, variability of contrast influences across different individuals/machines limits our ability to draw definitive conclusions, and warrants future studies that allow for better contrast control in lab-based environments, as well as extending the commonly used matching and categorization paradigms to probe for more specific perceptual processes such as sensory integration (Scheller & Sui, 2022b) or early visual, temporal filtering (Constable, Welsh, et al, 2019; Truong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the findings of the present study align with the mixed evidence of SPE arising at perceptual levels of information processing (Constable, Rajsic, et al, 2019; Golubickis et al, 2018; Macrae et al, 2017; Reuther & Chakravarthi, 2017; Sui et al, 2012; Stein et al, 2016), they suggest that part of the mixed findings regarding perceptual effects on self-prioritization may hinge on use of specific stimuli. At the same time, due to the online nature of the study, variability of contrast influences across different individuals/machines limits our ability to draw definitive conclusions, and warrants future studies that allow for better contrast control in lab-based environments, as well as extending the commonly used matching and categorization paradigms to probe for more specific perceptual processes such as sensory integration (Scheller & Sui, 2022b) or early visual, temporal filtering (Constable, Welsh, et al, 2019; Truong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite lacking evidence for their direct comparability, both types of self-associations have been shown to enhance information processing across multiple hierarchical processing stages. That is, attaching self-relevance to external information facilitates the selection and integration of perceptual information (Macrae et al, 2017, 2018; Scheller & Sui, 2022b; Sui, Yankouskaya, et al, 2015; Sui & Humphreys, 2015b; Truong et al, 2017), enhances the linking of attention and decision-making (Constable, Welsh, et al, 2019; Hu et al, 2020; Humphreys & Sui, 2016; Li et al, 2022; Liu et al, 2016), and leads to a more efficient binding of information in memory (Conway, 2005; Cunningham et al, 2008; Leshikar et al, 2015; Rogers et al, 1977; Yin et al, 2019). For example, in a previous study using the stimulus-label matching task, Sui and colleagues (Sui et al, 2012, Experiment 4) manipulated the luminance contrast of abstract shape stimuli that have been associated with the self, a friend, and a stranger.…”
mentioning
confidence: 99%
“…Notably, an interaction for the accuracy was found in the recognition task. Given a different level of social salience for self-vs. other-referential processing ( Sui et al, 2012 ; Scheller and Sui, 2022 ) and another person’s emotional face [A reviewer for Yiend (2010) ], the recognition task suggested that the prioritization of social salience could facilitate memory following attention orienting. Previous studies ( Bayliss and Tipper, 2006 ; Dodd et al, 2012 ) have shown an enhanced depth of encoding for valid targets, including incidental episodic memory and affective judgement, under gaze cues but not arrow cues.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is a possibility that a difference between self-and other-referential processing is also reflected in the level of social salience ( Sui et al, 2012 ; Scheller and Sui, 2022 ). Social salience is inherent in self-referential as well as emotional information such as what is attractive or dangerous.…”
Section: Introductionmentioning
confidence: 99%
“…Performance was better for the self-related shape than for the friend-, or stranger-related shapes. This self-bias towards abstract, temporarily self-associated stimuli is equivalent to the self-bias towards long-term self-associated stimuli such as names (Scheller & Sui, 2022).…”
Section: Introductionmentioning
confidence: 99%